Research Octane Number Improvement of Iraqi Gasoline by Adsorption of n-Paraffins Using Zeolite Molecular Sieves - Sadoon Ahmedzeki, Nada; Salah Alddin Mahdi, Arowa (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
This study focused on the improvement of the quality of gasoline and enhancing its octane number by the reduction of n-paraffins using zeolite 5A. This study was made using batch and continuous mode. The parameters which affected the n-paraffin removal efficiency for each mode were studied. Temperature (30 and 40 ˚C) and mixing time up to 120 min for different amounts of zeolite ranging (10-60 g) were investigated in a batch mode. A maximum removal efficiency of 64% was obtained using 60 g of zeolite at 30 ˚C after a mixing time 120 min. The effect of feed flow rate (0.3-0.8 l/hr) and bed height (10-20 cm) were also studied in a continuous mode. The equilibrium isotherm study was made using different amounts of zeolite (2-20 g) and then simulated for n-hexane and n- heptane using Langmuir, Freundlich isotherms. Kinetic of the adsorption of n-hexane and n-heptane was investigated using pseudo first order, pseudo second order and intra particle model. The Research octane number (RON) for some selected samples was measured to show the effect of the removal on the quality improvement of gasoline. Results showed an increase of 5.5 units in RON using 40 g zeolite at 40 ˚C and after 120 ˚C min. also an increase in 7 units was obtained in the continuous mode after 30 min using flow rate of o.3 l/hr and bed height of 10cm. Experimental data for n-hexane and n-heptane was found to fit Langmuir isotherm with correlation coefficient of 92.7% and 88.8% for n-C7 and n-C6, respectively. Adsorption of n-hexane and n-heptane was found to follow second order kinetics with correlation coefficient of 99.9% and 99.8% for n-C7and n-C6 respectively. This study revealed a favorable adsorption of n-paraffins on zeolite 5A as indicated by the separating factor of 0.6 and 0.44 for n-C7and n-C6, respectively.